(untitled) (Journal of Applied Learning and Teaching, 2024)
A look at social media platforms and media headlines, confirms that public discourse feature matters pertaining to well-being, altruism, benevolence, compassion, and community health. In our complex and rapidly changing world, the importance of kindness in society has become increasingly evident. A surge of interest in kindness can be aligned to the 2019-2022 pandemic, during which the global community sought avenues to demonstrate kindness to others and themselves. Whilst the concept of kindness dates to the 13th century, it has increasingly permeated everyday conversations, particularly in the aftermath of the pandemic. Despite its popularity, kindness lacks a precise scholarly definition, leaving uncertainty about its impact on teaching, learning, and research in higher education contexts. This paper aims to explore this gap by (a) reviewing existing research on kindness in higher education and (b) proposing a research agenda to guide future investigations. A systematic literature review (SLR), guided by the frameworks of Fox and Diezmann (2007, 2017) and Fox and Smith (2023), was conducted to examine the presence of kindness in higher education research literature and identify any prevailing themes.